Burghers in the Church, a Church in the TownChurch of St Bartholomew in Rakovník and Its Historical Development in the Context of the Town Life from the Middle Ages to the Mid-19th Century - Nachtmannová, Alena (Památky středních Čech, 2024)
The article deals with the Church of St Bartholomew in Rakovník and its historical role within the town's social structure. It analyses the development of the church from the Middle Ages to the mid-19th century, exploring its function as a religious, cultural, and social centre of the town. Not only did it provide a spiritual space, but it was also a place of social meetings, town ceremonies, and a symbol of town identity. The study mostly draws from the archival sources of the municipal and deanery archives of Rakovník.
Keywords: Church of St Bartholomew in Rakovník - church architecture - history of towns in the Middle Ages and early modern times - burgers' testaments - Hussitism - Literate Brotherhood